Longitudinal CSF Findings in Autoimmune Encephalitis—A Monocentric Cohort Study - Zrzavy, Tobias; Höftberger, Romana; Wimmer, Isabella; Berger, Thomas; Rommer, Paulus; Macher, Stefan (Frontiers in Immunology, 2021)
Autoimmune encephalitis (AIE) poses a diagnostic challenge due to its heterogeneous clinical presentation, which overlaps with various neurological and psychiatric diseases. During the diagnostic work-up, cerebrospinal fluid (CSF) is routinely obtained, allowing for differential diagnostics as well as for the determination of antibody subclasses and specificities. In this monocentric cohort study, we describe initial and serial CSF findings of 33 patients diagnosed with antibody-associated AIE (LGI1 (n=8), NMDA (n=7), CASPR2 (n=3), IgLON5 (n=3), AMPAR (n=1), GAD65/67 (n=4), Yo (n=3), Ma-1/2 (n=2), CV2 (n=2)). Routine CSF parameters of 12.1% of AIE patients were in normal ranges, while 60.6% showed elevated protein levels and 45.4% had intrathecal oligoclonal bands (OCBs). Repeated CSF analyses showed a trend towards normalization of initial pathological CSF findings, while relapses were more likely to be associated with increased cell counts and total protein levels. OCB status conversion in anti-NMDARE patients coincided with clinical improvement. In summary, we show that in routine CSF analysis at diagnosis, a considerable number of patients with AIE did not exhibit alteration in the CSF and therefore, diagnosis may be delayed if antibody testing is not performed. Moreover, OCB status in anti-NMDAR AIE patients could represent a potential prognostic biomarker, however further studies are necessary to validate these exploratory findings.